Factors Related to Sleep Quality in Patients After Laparotomy - Restu Gentari; Sunarsih; Gustop Amatiria; Ririn Sri Handayani (NERSI: Jurnal Keperawatan Indonesia, 2025)
In 2012, surgical procedures in Indonesia reached 1.2 million. In fact, in 2009, based on data from the Indonesian Ministry of Health, surgical procedures ranked 11th in terms of frequency (Indonesian Ministry of Health 2009 in Angraini, 2018).  Patients who have undergone surgery often experience sleep disturbances. Patients often wake up during the first night after surgery due to the reduced effects of anesthesia. Sleep is one of the basic human needs that is included in physiological needs. Sleep is also universal because all individuals, wherever they are, need sleep. The purpose of this study is to determine the factors related to the sleep quality of post-laparotomy surgery clients. This is a quantitative analytical research design. The sampling technique used non-probability sampling with 95 respondents. Data collection used the PSQI (Pittsburgh Sleep Quality Index) measurement tool. The data obtained by the researcher showed that there was a relationship between factors and the sleep quality of post-laparotomy patients. With 95 respondents, the results showed that there was a relationship between the comfort of the treatment room and sleep quality, then there was a relationship between anxiety and sleep quality, and there was a relationship between pain and sleep quality, where all three factors had a p-value of 0.000. Keywords: factors affecting sleep quality, post-laparotomy surgery